Synthesis Of Butyl Acetate By Lipase-Catalysed Esterification - Sim, Wan Ting (Universiti Sains Malaysia, 2021)
Ester is an aromatic compound naturally found in plants and fruits, which is animportant additive for food, beverages, pharmaceutical and cosmetic industries, giving flavour and fragrance. The compound is either supplied by natural resources or chemical synthesis. Lipase as biocatalyst shows great potential in aroma ester synthesis since lipase-catalysed reaction product is verified to be natural. In this study, butyl acetate was synthesised from acetic acid and n-butanol esterification catalysed by immobilized Candida rugosa lipase. Theprocess parameters which were optimized included reaction time, enzyme amount, temperature, and acetic acid/ethanol molar ratio were studied using one-factor-at-a-time (OFAT) method. Optimal molar conversion for butyl acetate of 81.33 % was obtained at 40 minutes incubation time with 50 U/ml of enzyme amount and substrate molar ratio of 1:1 (0.1 M) at 40 ℃ and 150 rpm. The kinetic parameters were also calculated using secondary data extracted from another researcher group. The data was fitted into Random Bi Bi, Ordered Bi Bi and Ping Pong Bi Bi mechanisms to compare the kinetic parameters obtained. The kinetic analysis of the esterification reactions was found to follow a Ping Pong Bi Bi mechanism with inhibition by one of the substrates, acetic acid. The fitted kinetic parameters obtained were Vmax = 249.05 mol/min.g, K m(A) = 46.25 mol/dm3 , K m(B) = 4.15 mol/dm3, KI = 15.09 mol/dm3.